The influence of Christianity on Graeco-Roman medicine up to the Renaissance - Francois P. Retief; Louise Cilliers (Acta Theologica)
In this overview of the effect of early Christianity on empirical medicine in Graeco-Roman times, it is shown that the first two centuries represented peaceful cooperation, since the Christians saw secular medicine as a legitimate form of supernatural cure and not as magic. Christianity brought caring communities with indiscriminate personalised care for the ill and aged. This ultimately led to the creation of hospitals as we know them today. Monastic institutions appeared which often had hospitals, and provided a degree of medical scholarship. When Christianity became the state religion in the 4th century, the Church Fathers became increasingly authoritarian regarding the practice of medicine which was to be based on their interpretation of Galen. Progressive stagnation of scientific development and medicine specifically, set in. However, during the 5th century Nestorian Christians, fleeing from persecution by the Church, settled in Persia where they initiated a  blossoming of medical science during the Golden Age of Islam (8th to 13th centuries), coexisting with the Dark Ages of Medieval Europe. After this period Jewish and Christian doctors reintroduced Arabic versions of the works of the Greek masters from the teaching hospitals of Islam to the young European medical schools at Palermo and Montpellier. The Church which had in the mean time persisted with antiquated dogmas, resented the new teachings from heathen Islam, and responded with reactionary measures against supposed heretics, inter alia by instituting the Inquisition. But after the Reformation and Henry VIII of England’s break with the Vatican, the hegemony of the Church had come apart and Christianity and medicine gradually became realigned according to the realities of the Age of Enlightenment.